2016
DOI: 10.1038/sc.2015.227
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin suppresses NLRP3 inflammasome activation and attenuates histopathology in a rat model of spinal cord injury

Abstract: Study design: Randomized experimental study. Objectives: To investigate the molecular mechanisms of quercetin in spinal cord injury (SCI) rats. Setting: China. Methods: One hundred female Sprague-Dawley rats were randomly assigned into four groups: sham group, SCI group, SCI+Vehicle (Veh) group, and the SCI+Quercetin (Que) group. The influences of quercetin on proinflammatory cytokine levels, histological changes and locomotion scale were estimated. Results: SCI significantly promoted nucleotide-binding domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 39 publications
(54 reference statements)
4
53
0
Order By: Relevance
“…NLRP3 inflammasome promotes diabetes‐induced endothelial inflammation and atherosclerosis . Studies have reported that quercetin inhibits NLRP3 inflammatory activation in a rat spinal cord injury model . Targeting adjustment of the NLRP3 inflammasome protect the nerve damage in spinal cord injury rats .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLRP3 inflammasome promotes diabetes‐induced endothelial inflammation and atherosclerosis . Studies have reported that quercetin inhibits NLRP3 inflammatory activation in a rat spinal cord injury model . Targeting adjustment of the NLRP3 inflammasome protect the nerve damage in spinal cord injury rats .…”
Section: Introductionmentioning
confidence: 99%
“…35 Studies have reported that quercetin inhibits NLRP3 inflammatory activation in a rat spinal cord injury model. 36 Targeting adjustment of the NLRP3 inflammasome protect the nerve damage in spinal cord injury rats. 37 Previous studies have demonstrated that quercetin can up-regulate SIRT1 leading to neuroprotection and improve glycolipid metabolism.…”
mentioning
confidence: 99%
“…In flavones, both rutin and its aglycone, quercetin, also exhibited neuroprotective effects against SCI. Intraperitoneally injection of rutin and quercetin reduced production of ROS and proinflammatory mediators, and NLRP3 inflammasome components including NLRP3, ASC, and caspase‐1 in the rats with SCI …”
Section: Health Promoting Potentials Of Dietary Phytochemicalsmentioning
confidence: 99%
“…Intraperitoneally injection of rutin and quercetin reduced production of ROS and proinflammatory mediators, and NLRP3 inflammasome components including NLRP3, ASC, and caspase-1 in the rats with SCI. [108,109] Oxidative stress has emerged as a deleterious factor in IS and a prospective cohort study provides evidence to show the protective effects of higher consumption of fruits and vegetables, in particular cruciferous and green leafy vegetables and citrus fruits, against risk of IS. [110] Anthocyanins belong to a class of flavonoids that are natural water-soluble colorants widely distributed in berries, grapes, and cherries.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Similarly, in a collagen-induced model of arthritis, quercetin inhibited inflammasome activation and associated inflammatory induction (Yang et al, 2018). The administration of the polyphenol quercetin prior to spinal cord injury in mice, which similarly decreased NLRP3 mediated cytokine production through the downregulation of ROS (Jiang et al, 2016). In a rat model of diabetes, increased intracellular ROS upregulated the thioredoxin-interacting protein (TXNIP), which facilitates activation of the NLRP3 inflammasome.…”
Section: Grape-derived Polyphenolic Compounds Attenuate Risk Factors mentioning
confidence: 99%